Hormonal Fluctuations during the Estrous Cycle Modulate Heme Oxygenase-1 Expression in the Uterus - Zenclussen, Maria L.; Casalis, Pablo A.; Jensen, Federico; Woidacki, Katja; Zenclussen, Ana C. (Frontiers in Endocrinology, 2014)
Deletion of the Heme Oxygenase-1 (Hmox1) locus in mice results in intrauterine lethality. The expression of the heme catabolyzing enzyme encoded by this gene, namely HO 1, is required to successfully support reproductive events. We have previously observed that HO-1 acts at several key events in reproduction ensuring pregnancy. HO-1 defines ovulation, positively influences implantation and placentation and ensures fetal growth and survival. Here, we embarked on a study aimed to determine whether hormonal changes during the estrous cycle in the mouse define HO-1 expression, thus influencing receptivity. We analyzed the serum levels of progesterone and estrogen by ELISA and HO-1 mRNA expression in uterus by real time RT-PCR at the metestrus, proestrus, estrus and diestrus phases of the estrous cycle. Further, we studied the HO-1 protein expression by Western Blot upon hormone addition to cultured uterine AN3 cells. We observed that HO-1 variations in uterine tissue correlated to changes in hormonal levels at different phases of the estrus cycle. In vitro, HO-1 protein levels in AN3 cells augmented after the addition of physiological concentrations of progesterone and estradiol, which confirmed our in vivo observations. Our data suggest an important role for hormones in HO-1 regulation in uterus that has a significant impact in receptivity and later on blastocyst implantation.